THE EFFECT OF THE ALTITUDE ZONE ON COGNITIVE FUNCTION FOR MALE PILOTS IN INDOCTRINATION AND AEROPHYSIOLOGY TRAINING IN 2019 - HERATIKA, DEBY; KEKALIH, ARIA; MULYAWAN, WAWAN; AGUSTINA, AMILYA; SOEMARKO, DEWI SUMARYANI; SIAGIAN, MINARMA (International Journal of Applied Pharmaceutics, 2020)
Objective: A pilot on duty at altitude can be exposed to hypoxia, both mild and severe. The incidence of hypoxia on a flight can be fatal, especially if hypoxia is experienced by a pilot on duty. One manifestation of hypoxia is decreased cognitive function. A pilot is required to carry out multitasking operations using cognitive functions, especially in an emergency. Therefore, decreased cognitive function due to hypoxia in a pilot can cause accidents in flight. This study aims to determine changes in cognitive function with hypoxia exposure at several altitude zones. Methods: This study used an experimental one-group pretest-posttest design. The subjects were 31 military pilots who participated in Indoctrination and Aerophysiology Training. Subjects filled 6 Cognitive Impairment Test (6 CIT) questionnaires at ground level, efficient physiological zone (10,000 ft), and physiological deficient zone (25,000 ft) in a hypobaric chamber. Results: There was a change of 6 CIT score at 10.000 ft compared to ground level (Friedman post-hoc Wilcoxon, P = 0.001). There was also a change of 6 CIT score at 25,000 ft compared to ground level (Friedman post-hoc Wilcoxon, P<0.001). Conclusion: There was a change in cognitive function in the efficient physiological zone and physiological deficient zone, compared to ground level.